PERCEPTIONS OF GRADE XII STUDENTS TOWARDS THE IMPLEMENTATION OF COMPUTER BASED TESTS (CBT) IN SENIOR HIGH SCHOOLS - Manahil Raiqamahin br Sebayang; Asyifa Zhafirah Akmal; Fatimah Zahrah Siregar; Shafa Atifah; Zulfa Rahmi Pandia (PT. Radja Intercontinental Publishing, 2025)
The rapid advancement of information technology has significantly transformed educational evaluation systems, one of which is the implementation of Computer-Based Testing (CBT). This assessment method is considered more efficient and capable of accelerating the evaluation process; however, its effectiveness largely depends on technical readiness and user experience. This study aims to analyze Grade XII students’ perceptions of CBT implementation, focusing on aspects such as interface design, question navigation, system speed, security, and technical support. Employing a quantitative survey method, data were collected through structured questionnaires and analyzed descriptively. The findings indicate that most students expressed positive perceptions, particularly regarding the user-friendly interface, ease of navigation, and time efficiency. Nevertheless, system performance stability and the responsiveness of technical support were identified as key areas that require improvement. Overall, CBT demonstrates strong potential as an effective and credible assessment system, provided that it is supported by reliable infrastructure and responsive technical assistance. The results of this study are expected to contribute valuable insights for schools and policymakers in enhancing digital readiness and improving user experience in future CBT implementations